Contribution of home gardens from the Sustainable Reserve Food Garden Program in Pacitan Regency: Supporting nature conservation - Titik Wijayanti; Diyah Ayu Widyaningrum; Trio Ageng Prayitno; Nikmatul Iza (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
The Sustainable Reserve Food Garden Program is one of the government’s strategies to support household food security and environmental conservation. This study aims to assess the contribution of home gardens resulting from the home garden sustainability program to nature conservation efforts in Pacitan Regency, East Java. The analyzed indicators include cultivation practices, utilization of local plant species, resource efficiency, environmentally friendly farming, plant density, and the Shannon-Wiener diversity index. This descriptive-observational study employed a mixed-methods approach, integrating quantitative ecological measurements with qualitative data collected through direct field observations, structured interviews, and questionnaires involving 300 household participants. Quantitative analysis included the Shannon-Wiener diversity index, plant density measurements, descriptive statistics, and Principal Component Analysis, while qualitative information supported the interpretation of household conservation practices. The results show that home gardens significantly contribute to the conservation of local genetic resources and increase household-level biodiversity. Principal Component Analysis revealed clusters of respondents based on their level of conservation contribution. The majority were classified as “successful” in integrating food production and conservation functions. These findings emphasize the importance of promoting home gardens as sustainable micro-conservation spaces at the household level.